Violence Victimization, Homelessness, and Severe Mental Illness Among People Who Use Opioids in Three U.S. Cities - Hong, Chenglin (Journal of interpersonal violence, 2023)
This study examined the associations between violence victimization, homelessness, and severe mental illness (SMI) among people who use opioids (PWUOs) in three U.S. cities. We analyzed data from a cross-sectional survey conducted from May 2019 to February 2020 across three study sites: Los Angeles, CA; Las Vegas, NV; and Atlanta, GA. We used multivariable regressions to examine how multiple victimizations and housing situation are associated with SMI. Based on K-6 scale, nearly half (44.2%) were screened positive for SMI. Meanwhile, 69.7% of the participants reported experiencing some kind of violence in their lifetime, and more than half (51.9%) reported experiencing recent violence (in the past 6 months). The most common form of lifetime violence was emotional (59.5%), followed by physical and intimate partner violence (IPV) (56.1 and 34.9%, respectively), and 34.9% of all participants reported experiencing multiple forms of victimization in the past 6 months. Participants who reported homelessness were more likely to report having experienced recent violence victimization (p < .001). In multivariable models, experiencing recent victimization was significantly associated with SMI (adjusted odds ratio (AOR) = 1.85, 95% confidence interval [CI] [1.46, 2.38]), as was homelessness (AOR = 1.57, 95% CI [1.15, 2.14]), after adjusting for study covariates. Among those with moderate and SMI (n = 927), only 22% were currently receiving mental health services, and those who reported having experienced any forms of violence in the past 6 months were more likely to utilize mental health services than those who had not experienced any recent violence victimization (25 vs. 17.9%, p < .05). To improve mental health and wellness among this high priority population, mental health facilities and syringe service programs may consider screening for experiences of violence and using trauma-informed mental health approaches. Harm reduction interventions must be responsive to the diverse individual and structural-level needs of PWUOs, especially those experiencing homelessness and housing insecurity. Holistic strategies and services are needed to meet the social and structural needs of this population.